Comparison between ternary and binary Gray-code based phase unwrapping methods - Zheng, Dongliang (2018)
Phase-shifting profilometry using binary patterns with projector defocusing has been widely used for high-speed 3D measurement. Recently, a ternary Gray-code based phase unwrapping method has been proposed, which enables to accurately unwrap the phase but reduces the required binary patterns. This paper presents a comparison between the ternary and the traditional binary Gray code-based phase unwrapping methods.